(untitled) (Global Journal of Human-Social Science, 2023)
Bangladesh has seen a significant rise in the number of young people who run businesses on social media sites This trend has been noted in recent years This is a significant contribution to the nation s economy since young people constitute a significant proportion of the total population The purpose of the study is to determine how social media assists young people in starting their enterprises and in educating the younger generation about the difficulties and opportunities that can help improve Bangladesh s economy In addition a questionnaire-based study was conducted to determine whether a low initial investment cost a high-profit ratio simple and direct payment methods and sufficient networking opportunities make businesses more attractive to young entrepreneurs This paper shows that young entrepreneurs are becoming more interested in social-media based business because it gives them a chance to make money and work for themselves